2021
DOI: 10.1136/medhum-2021-012141
|View full text |Cite
|
Sign up to set email alerts
|

Waiting, strange: transplant recipient experience, medical time and queer/crip temporalities

Abstract: People who receive a ‘solid’ organ transplant from a deceased person may experience imaginative challenges in making sense of how the transfer impacts their own past and future, as shown in existing scholarship. Building on such work, this article considers how the temporalities of medical encounter itself may also become temporally ambiguous, posing representational challenges both pre-transplantation and post-transplantation. The dominant narrative of transplant in transplantation journals and hospital commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…We have demonstrated that significant moments in the transplant or donation journey are multiple, highly emotional and associated with uncertainty. As shown by Wasson, the transplant experience does not correspond to medical temporality, where the procedure is described as a “healing moment.” 28 Transplantation is characterized by a non-linear temporality, “post-transplant time as still profoundly structured by waiting, expectation and suspense, the transformed body less healed than permanently contingent and fragile in different ways.” 28 As our participants reported, the experience is also perceived as lonely. We can assume that the high intensity, uncertainty and loneliness of the lived experience of transplantation or donation lead to a search for experiential learning and support from the self-narratives of peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated that significant moments in the transplant or donation journey are multiple, highly emotional and associated with uncertainty. As shown by Wasson, the transplant experience does not correspond to medical temporality, where the procedure is described as a “healing moment.” 28 Transplantation is characterized by a non-linear temporality, “post-transplant time as still profoundly structured by waiting, expectation and suspense, the transformed body less healed than permanently contingent and fragile in different ways.” 28 As our participants reported, the experience is also perceived as lonely. We can assume that the high intensity, uncertainty and loneliness of the lived experience of transplantation or donation lead to a search for experiential learning and support from the self-narratives of peers.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Wasson, the transplant experience does not correspond to medical temporality, where the procedure is described as a "healing moment." 28 Transplantation is characterized by a non-linear temporality, "post-transplant time as still profoundly structured by waiting, expectation and suspense, the transformed body less healed than permanently contingent and fragile in different ways." 28 As our participants reported, the experience is also perceived as lonely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the pre-transplantation evaluation phase is often experienced as a particularly exciting, dynamic and constructive process, the concretization of the therapeutic plan in the case of eligibility is often followed by a period of distress. The indefinite period of waiting for the operation, feelings of impatience, discouragement and anxiety, including worries about the donor’s death, the graft’s engraftment and the necessary post-transplant medical regimen, create uncertainty and raise questions about the healing effect of the transplant ( 31 , 32 ). Communicating these concerns and uncertainties to members of the transplantation team is often hampered by patients’ fears that such discussions will affect their eligibility for transplantation ( 33 ).…”
Section: Pancreas Transplantation and Psychological Issuesmentioning
confidence: 99%
“…For Wasson, Nancy's L'Intrus moves beyond a linear narrative of illness and cure in that it '[conveys] the unfinishedness of transplant'. 26 Wasson explores how the patient's experience of time and of waiting involved in transplant results in the space of the hospital itself becoming warped: 'the times of medical intervention, too, may become strange. Recipients' experiences of hospital, pharmacology and daily self-monitoring may be disorientating and resist conventional conceptions of temporalities of cure'.…”
Section: Nancy Illness Medicine and Spacementioning
confidence: 99%